Zambia Economic Brief, October 2013 : Zambia's Jobs Challenge--Realities on the Ground - World Bank (Washington, DC, 2014)
Zambia shares its robust economic growth and capital inflows in the past few years with other Sub-Saharan countries, growth supported by high commodity prices that while declining are still at historical high levels. High commodity prices have induced large foreign direct investment (FDI) flows, mainly in extractive industries but also in services sector, supporting growth. Zambia's mining sector has benefited from FDI, receiving almost 1 billion dollar in 2011 alone. A large gap has emerged between available resources and likely spending in 2013. The government is responding with a full range of adjustments, including cutting recurrent spending (such as on travel and motor vehicles), cutting capital projects, and stepping up revenue collection. The government has raised fuel prices and reduced maize and fertilizer subsidies, but the medium-term fiscal impact of these initiatives is uncertain. These reforms aimed to create space for expanding better targeted spending programs. Zambia's economy has seen far too many unexpected policy changes in recent years. Persistent and even escalating perceptions of an uncertain policy environment can weaken investment, thereby reducing gross domestic product (GDP) growth. Zambia's population and labor force is young and growing fast. The current structure of the economy and sources of growth are such that formal wage jobs are being created slowly. Creating formal jobs in the private sector is rightly accorded top priority in government policy and strategy documents. The government's general approach is to provide an enabling environment for the private sector and address constraints to growth. For wage employment, understanding the technical and vocational education sector is a priority for future skills development. There is a need to address the gaps in access to basic education and prevent dropouts through targeted programs for children at risk of not starting or finishing school. This report is divided in two sections: section one gives recent economic developments and section two presents jobs challenge: realities on the ground.